Assisting Santri Communities in Enhancing Understanding of Surah Yasin and Tahlil Recitation - Munawaroh, Hidayatul; Mubtadik, Mohamad Ayyub; Rahmania, Nia; Sulaeman, Maryam; Novitasari, Ifit; Khan, Sayyid Yusuf (STAI Miftahul ULa Nganjuk, 2024)
This community service project aims to enhance religious understanding and character development among santri through the regular practice of reading Surah Yasin and memorizing tahlil at TPQ Tarbiyatus Sibyan, Dusun Dingin Ngronggot. The issue addressed is the lack of awareness among children in the community about the significance of reading Surah Yasin and tahlil, and their application in daily life. The focus of the service is on routine learning of Surah Yasin and tahlil, involving santri in leading the activities. The methodology employed is Asset-Based Community Development (ABCD), utilizing local assets such as the TPQ and active community engagement. The results indicate that this practice effectively improved the religious understanding of the santri, created positive daily habits, and fostered character development through reward systems and leadership opportunities. This initiative also led to social changes, with increased active participation of santri in religious activities.